The incidence and burden of hospital-treated sports-related injury in people aged 15+ years in Victoria, Australia, 2004–2010: a future epidemic of osteoarthritis?. Issue 7 (July 2015) - Finch, C.F.; Kemp, J.L.; Clapperton, A.J.
Summary: Objectives: Previous sports injury is a known risk factor for subsequent osteoarthritis (OA), but population-based rates of sports injury are unknown. The aims of this study were to: (1) describe the trends in the population incidence and burden of all hospital-treated sports injury in Victoria, Australia in adults aged 15+ years; (2) determine the incidence of lower limb and knee injuries; and (3) quantify their population health burden as average direct hospital costs per injury and lengths of stay. Methods: Health sector data relating to adults aged 15+ years, for 2004–2010 inclusive, was extracted from the Victorian Admitted Episodes Dataset (VAED) and Victorian Emergency Minimum Dataset (VEMD). Data relating to sports injuries were identified using activity codes in each dataset Trends in injury frequency and rates were determined, and economic burden was calculated. Results: The overall annual rate of hospital treated sports injuries increased by 24% ( P = 0.001), and lower limb injuries by 26% ( P = 0.001) over the 7 years. The associated accumulated economic burden was 265 million for all sports injuries and 110 million for lower limb injuries over the 7-years. Conclusions: The findings of this study show a significant increase in sports injuries in the state of Victoria, Australia over a 7-year period. As previous sports injury is a risk factor for the development of OA, the future incidence of OA will escalate, placing an even greater burden on health care systems. Population-wide preventative strategies that reduce the risk of sports injury are urgently required in order to reduce the future burden of OA.